Solution to the Homogeneous Boundary Value Problems of Free Vibrations of a Finite String - Dolya, P.G. (Журнал математической физики, анализа, геометрии, 2008)
In the paper solutions to the homogeneous boundary value problems of free vibrations of a nite string are obtained in the d'Alembert form. The initial boundary value problems to vibrations of a string with free ends as well as with one end xed and one free are solved.